School, discourse and sexuality: an analysis of el Vestido Nuevo - Alexandre Sebastião Ferrari Soares; Dantielli Assumpção Garcia (Travessias, 2017)
Based on discourses that are naturalized in society and therefore at school, we intend to demonstrate, in accordance with the French Discourse Analysis theoretical framework, how some statements work discursively. Our aim is to scrutinize particularly the way in which sexist, homophobic and binary statements that establish an existing causal relation between biological sex, gender and identity determine characteristics and functions for genders. In view of this, we propose the analysis of a Spanish short film called El Vestido Nuevo.